Bld10p/Cep135 determines the number of triplets in the centriole independently of the cartwheel. (12th September 2022) - Noga, Akira; Horii, Mao; Goto, Yumi; Toyooka, Kiminori; Ishikawa, Takashi; Hirono, Masafumi
Abstract: The conserved nine‐fold structural symmetry of the centriole is thought to be generated by cooperation between two mechanisms, one dependent on and the other independent of the cartwheel, a sub‐centriolar structure consisting of a hub and nine spokes. However, the molecular entity of the cartwheel‐independent mechanism has not been elucidated. Here, using Chlamydomonas reinhardtii mutants, we show that Bld10p/Cep135, a conserved centriolar protein that connects cartwheel spokes and triplet microtubules, plays a central role in this mechanism. Using immunoelectron microscopy, we localized hemagglutinin epitopes attached to distinct regions of Bld10p along two lines that connect adjacent triplets. Consistently, conventional and cryo‐electron microscopy identified crosslinking structures at the same positions. In centrioles formed in the absence of the cartwheel, truncated Bld10p was found to significantly reduce the inter‐triplet distance and frequently form eight‐microtubule centrioles. These results suggest that the newly identified crosslinks are comprised of part of Bld10p/Cep135. We propose that Bld10p determines the inter‐triplet distance in the centriole and thereby regulates the number of triplets in a cartwheel‐independent manner. Synopsis: The nine‐fold centriole structure is likely formed through dynamic interaction between cartwheels and circularly‐arranged microtubules formed independently of the former. Here, Bld10p/Cep135 is shown to determine the number of microtubules by crosslinking the triplet A‐tubules. Truncation of Chlamydomonas Bld10p reduces inter‐microtubule distance and frequently produces eight‐microtubule centrioles in the absence of the cartwheel. Bld10p is localized on and between the pinheads located at the junction of the A‐tubule and cartwheel spoke. Novel crosslinks are found between the pinheads by conventional and cryo‐electron microscopy. Abstract : Electron microscopy and mutant analyses show that a conserved centriolar protein that connects spokes and triplet microtubules plays a key role in the cartwheel‐independent mechanisms for ensuring nine‐fold symmetry.